An improved RF and gradient coil system for high resolution in vivo guinea pig cochlea imaging on a 3T clinical magnet. Issue 4 (23rd March 2015) - Kaggie, Joshua D.; Goodrich, K. Craig; Kim, Seong‐eun; Beck, Michael J.; Parker, Dennis L.; Merrill, Robb; Abele, Travis A.; Wiggins, Richard; Oakley, Gretchen M.; Hadley, J. Rock
ABSTRACT: Purpose: The purpose of this work was to develop and evaluate a system consisting of an insertable gradient, RF coils, and animal positioning hardware to enable imaging of the internal structure of the cochlea and other inner ear structures of a guinea pig model at 3T. Methods: Transmit and receive RF coils, and an animal positioning system, were developed and integrated with an insertable gradient and animal monitoring system for improved guinea pig cochlea imaging when compared to a standard clinical 3T MRI system. A resolution phantom with 120 μm line separations was used to assess the contrast improvements with the insertable gradient. A homogeneous phantom was used to assess the SNR and homogeneity of the RF coils. FLASH imaging was used to observe the temporal passage of gadolinium contrast through the guinea pig cochlea. Results: The insertable gradient enabled increased resolution imaging with nearly twice the contrast‐to‐noise ratio. The small animal array had better SNR for imaging the guinea pig cochlea (about 14 mm deep) than the commercial Siemens wrist coil (2.2×) and the small birdcage coil (1.6×). The positioning device kept the animal secure and stationary. Injected gadolinium contrast allowed visualization of the internal cochlear structures with FLASH image acquisition, which achieved 100 μm isotropic resolution images in 33 min. Conclusion: The specialized RF coils and animal holding equipment designed to operate within the composite gradient enabled higher resolution images than could be obtained from the available RF coils operating in the conventional gradients on the clinical MRI system. © 2015 Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 44B: 89–101, 2015